Measuring students' plant awareness: A prerequisite for effective botany education - Pany, Peter; Meier, Florian D.; Dünser, Benno; Yanagida, Takuya; Kiehn, Michael; Möller, Andrea (Journal of biological education, 2024)
The term 'Plant Blindness' describes people tending to overlook plants, even though they have an enormous importance for life on earth, especially because of their ability to photosynthesise. Many attempts have been made to counteract plant blindness in biology education. However, so far there is no comprehensive tool to assess the degree of plant awareness (instead of plant blindness) in students. Here, plant awareness is conceptualised in four domains: (1) visual perception of plants, (2) categorising plants as living organisms, (3) knowledge about plants, and (4) attitudes towards plants. We present results from the two developed scales 'Plants as living organisms' and 'Knowledge about plants'. To test the new scales, 345 Austrian secondary school students took part in a questionnaire study. A confirmatory factor analysis indicates sufficient model fit. Results show that students consider plants as 'less alive' than animals but 'more alive' than bacteria. Those who attribute the characteristics of life to plants have more knowledge about plants, indicating that both domains of plant awareness might have a common basis. The development of a plant awareness questionnaire will eventually provide a powerful tool to investigate the effectiveness of learning environments fostering plant awareness, a prerequisite to reach the sustainable development goals.